ChemInform Abstract: I2‐Catalyzed Aerobic Oxidative C(sp3)—H Amination/C—N Cleavage of Tertiary Amine: Synthesis of Quinazolines and Quinazolinones. Issue 41 (October 2015) - Yan, Yizhe; Xu, Ying; Niu, Bin; Xie, Huifang; Liu, Yanqi
Abstract A novel iodine‐catalyzed aerobic cyclization of o‐carbonyl anilines (I) and structurally related o‐aminobenzamides (IV) with TMEDA (II) as one‐carbon source is developed to give quinazolines (III) and quinazolinones (V).